Foliar stomata characteristics of tree species in a university green open space (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Susilowati A, Novriyanti E, Rachmat HH, Rangkuti AB, Harahap MM, Ginting IM, Kaban NS, Iswanto AH. 2022. Foliar stomata characteristics of tree species in a university green open space. Biodiversitas 23: 1482-1489. Stomata, a gas regulatory system of leaves, provide a great chance to investigate the interaction between plants and their environment. Stomata consist of surrounded by two guard cells. Stomata are found in all parts of the plant that are exposed to the air, especially the leaves. In identifying a plant species, it is necessary to have epidermal characteristics such as stomata to complete the taxonomic data. Several studies have been conducted on the type of stomata on the leaves of some dicotyledonous and monocot plants, but not many have reported similar studies on green space. Universitas Sumatera Utara (USU) campus also plays an important function as green space (GS) in Medan City due to its richness in tree collection number and species. In line with the effort in o maximizing the role of trees as the core element of green space, exploring the characteristics of stomata is important to conduct. Therefore, this study aimed to analyze the leaf stomata characteristics of several tree species in the green open space of the USU campus. A total of 83 tree species were taken for their leaves to investigate the stomata characters. Three healthy mature leaves on the lower part of newly grown branches were collected from each plant. The replica and the nail polish method were employed for stomata slice making. The stomata type, length, wide, density and distribution were observed. The result showed that 83 tree species in the USU campus have varied stomata types, with the percentage were highest characteristic found in paracytic (91.46%), followed by anomocytic (6.02%), anisocytic (1.20%), and diacytic (1.20%). The longest stomata were observed in Antidesma bunius (32.04 ????????). The widest stomata were noticed in Garcinia mangostana (37.62 ????????). Meanwhile, the shortest and narrowest stomata were found in Shorea laevis, which were 5.43 ???????? and 3.72 ????????, respectively. The species with the highest stomatal density was Schleichera oleosa (4294 mm-2). According to the study, the tree species at USU generally have high stomata density, length, and width, making them more suitable for green space. Species with a high number and density of stomata and a large size are much more likely to adsorb pollutants such as carbon monoxide.